Measuring the added value of stock recommendations - Jones, H; Anderson, A; Martinez, J (European Finance Association, 2016)
Using data from the Stockholm Stock Exchange we study the value added by (as distinct from the abnormal returns to) analysts’ recommendations. Recommending brokers’ clients trade profitably around positive recommendations at the expense of the clients of brokers without analyst coverage. Significant profits come from transactions before recommendation dates. Value added is greatest for upgrades to large caps. Value added from downgrades and from recommendations for small caps is largely insignificant despite high abnormal returns to these categories. Brokers making profitable recommendations for their clients are rewarded by abnormal trading volumes, and capture much of the value added themselves.